Health at Work : Critical Perspectives. - Tomkins, Leah; Pritchard, Katrina (Critical approaches to health., 2019)
Engaging with some of the most debated topics in contemporary organizations, Health at Work: Critical Perspectives presents a critical, contingent view of the healthy employee and the very notion of organizational health. Drawing on expressions such as 'blowing a fuse', 'cracking under pressure' or 'health MOT', this book suggests that meanings of workplace health vary depending on how we frame the underlying purpose and function of organization. Health at Work takes some of the most powerful and taken-for-granted discourses of organization and explores what each might mean for the construction of the healthy employee. Not only does it offer a fresh and challenging approach to the topic of health at work, it also examines several core topics at the heart of contemporary research and practice, including technology, innovation, ageing and emotions. This book makes a timely contribution to debates about well-being at work, relevant to practitioners, policy-makers and designers of workplace health interventions, as well as academics and students. This book will be illuminating reading for students and scholars across management studies, occupational health and organizational psychology.